Let 3 x + 3 x 1 = 3 , then find the value of x 3 + x 3 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 3 x + 3 x 1 ) 3 x + 3 3 x + 3 x 3 + x 1 ⟹ x + x 1 = 3 3 = 2 7 = 2 7 − 3 ( 3 x + 3 x 1 ) = 2 7 − 9 = 1 8
Similarly,
( x + x 1 ) 3 x 3 + 3 ( x + x 1 ) + x 3 1 ⟹ x 3 + x 3 1 = 1 8 3 = 5 8 3 2 = 5 8 3 2 − 3 ( x + x 1 ) = 5 8 3 2 − 3 ( 1 8 ) = 5 7 7 8
We have ( x + x 1 ) 3 = x 3 + 3 ⋅ x 2 ⋅ x 1 + 3 ⋅ x ⋅ x 2 1 + x 3 1 = x 3 + x 3 1 + 3 ( x + x 1 ) ⟹ x 3 + x 3 1 = ( x + x 1 ) 3 − 3 ( x + x 1 ) .
So x + x 1 = ( 3 x + 3 x 1 ) 3 − 3 ( 3 x + 3 x 1 ) = 3 3 − 3 ⋅ 3 = 1 8
So x 3 + x 3 1 = ( x + x 1 ) 3 − 3 ( x + x 1 ) = 1 8 3 − 3 ⋅ 1 8 = 5 7 7 8
FullSimplify [ x 3 + x 3 1 /. Solve [ 3 x + 3 x 1 = 3 ] ] ⇒ { 5 7 7 8 , 5 7 7 8 }
x = 9 ± 4 5
Substitute y = x 3 1 giving y 2 − 3 y + 1 = 0 with the solution y = 2 1 ( 3 ± 5 ) , which substitutes easily into x 3 + x 3 1 giving y 9 + y 9 1 with a final value of 5778.
By the way, that is the surface temperature of the Sun in Kelvin.
Problem Loading...
Note Loading...
Set Loading...
use the identity a 3 + b 3 = ( a + b ) 3 − 3 a b ( a + b ) twice, i.e x + x 1 = ( 3 x + 3 x 1 ) 3 − 3 3 x 3 x 1 ( 3 x + 3 x 1 ) = 3 3 − 3 × 3 = 1 8 x 3 + x 3 1 = ( x + x 1 ) 3 − 3 x x 1 ( x + x 1 ) = 1 8 3 − 3 × 1 8 = 5 7 7 8